Ultrahigh transverse rupture strength in tungsten-based nanocomposites with minimal lattice misfit and dual microstructure. (February 2021) - Chakravarty, D.; Laxman, N.; Jayasree, R.; Mane, R.B.; Mathiazhagan, S.; Srinivas, P.V.V.; Das, R.; Nagini, M.; Eizadjou, M.; Venkatesh, L.; Ravi, N.; Mahapatra, D.R.; et al.
Abstract: New-generation structural materials with superior properties are a constant demand in applications involving extreme environments. Here, we demonstrate the fabrication of a high-strength, high-dense W-TaC-Ta2 O5 nanocomposite for such applications on a large scale by a simple, cost-effective, scalable, bottom-up powder metallurgy approach using plasma sintering. The first clear microstructural evidence of the scavenging effect of carbide particles in the W-MC composites (M = Ta, Zr, Hf, Ti) is demonstrated through atom probe studies. Localized plastic deformation and the unique stress-induced amorphization in tungsten are observed due to dislocation activities, and these phenomena are corroborated by molecular dynamics (MD) simulations. Optimized composition and processing conditions yield high Vickers hardness 540 HV10 and super-high transverse rupture strength (TRS) 1650 MPa, in upscaled components of 100 mm diameter. The enhanced mechanical properties are attributed to the cumulative effect of the grain boundary strengthening and dispersion strengthening from the refined tungsten grains and the second phase intragranular nanocrystalline particles, respectively, the coherent particle-matrix interfaces, the low oxygen-segregation at grain boundaries and the 'dual nanocrystalline-amorphous' microstructure present in the matrix. Graphical abstract: Unlabelled Image Highlights: W-TaC composites prepared by spark plasma sintering of size 100 mm diameter. High density, fine grains yield strength of 1650 MPa and hardness of 540 HV10 . Improved properties explained by grain boundary and dispersion strengthening. Scavenging effect of TaC for oxygen established through atom probe studies. Coherent particle/matrix interface and unique dual 'nano-amorphous' microstructure